Cardiovascular manifestation in hypothyroid patient: a cross-sectional study - Alam, Shahinul; Siam, Muhammad Masrur; Morshedul Alam Khan, M.; Ananya, Sadia Nusrat; Shajjad Hossain, D. M.; Shah Alam, M.; Begum, Fahmiah (International Journal of Research in Medical Sciences, 2025)
Background: Hypothyroidism exerts widespread physiological effects, including significant cardiovascular alterations. Both overt and subclinical hypothyroidism can impair cardiac function, although the severity and pattern of abnormalities may differ. The aim of the study was to evaluate the spectrum of cardiovascular manifestations among hypothyroid patients attending a tertiary care hospital. Methods: A total of 100 adults with newly diagnosed or previously known overt or subclinical hypothyroidism were enrolled. Patients with secondary hypothyroidism, major comorbidities, congenital or structural heart disease, chronic systemic illnesses, pregnancy, or relevant drug exposures were excluded. Clinical examination, ECG, and echocardiography were performed by trained cardiology specialists. Data were analyzed using SPSS-24. Results: The mean age of the patients was 38.89±9.98 years, and 81% were female. Overt hypothyroidism was present in 67% of participants. Common cardiovascular symptoms included dyspnoea (21%), ankle swelling (16%), and chest pain (4%). Bradycardia (36%), hypertension (27%), pedal edema (19%), and diminished heart sounds (23%) were notable clinical signs. ECG abnormalities included bradycardia (41%), low-voltage complexes (38%), flat or inverted T waves (25%), and ST-segment changes (26%). Echocardiographic findings showed LVDD (21%), RWMA (20%), pericardial effusion (12%), systolic dysfunction (9%), and reduced ejection fraction (11%). ST-segment changes (p=0.021) and systolic dysfunction (p=0.022) were significantly more frequent in overt hypothyroidism. Conclusions: Cardiovascular manifestations are common in hypothyroidism, with overt cases demonstrating more pronounced structural and functional abnormalities. Early detection and appropriate management are essential to prevent long-term cardiac complications.